Role of Foreign Investment In Economic Sectors - Ergashev Ilhomjon Ikromovich; Alimqulova Zarinabonu Ma’rufjon qizi (Research Parks Publishing LLC, 2022)
The article describes the modern methods of investing, which are the tools that characterize the sectors of the economy, and ways to overcome existing problems.